Celebrating Adam Watkins First Birthday in Watkins' Backyard - Watkins, Howard::::::::: (1979)
Peggy Sanders, Joanne Cordova, Norma Herman, Diane Shilton seated at patio table; Elaine Harris standing Elaine Harris in background